Does changing the bike frame influence pedal force pattern in mountain bike cyclists? - Devys, S.; Bertin, D.; Rao, G. (Science & Sports, 2019)
Objectives: In cycling, the interaction between the athlete and his bike is crucial for the resulting performance with frame geometry and bike-setup being known to affect the biomechanical and physiological outputs. Road and Olympic cross-country (XCO) bike frames are routinely used in training programs, despite having different frame configurations. The present study compared biomechanical indices of the pedalling techniques between road and off-road bike frames. Equipment and methods: Ten XCO mountain bikers of national level performed two sessions on their personal bikes. For each frame, the athletes achieved one-minute tests at 65%, 90% and 115% of their maximal aerobic power (MAP) while recording 3D pedal forces. Together with various frame and bike-setup measurements, the peak of effective force, corresponding crank angle, global and instantaneous index of efficiency were compared for Power and Frame statistical effect. Results: The frame geometry and bike-setup showed significant differences between the road and XCO frames. The Power factor significantly (P<0.05) influenced the biomechanical indices of pedalling technique, but no effect of the Frame on any variable was reported. We posit that an internal reorganization was adopted by each cyclist to retrieve a specific and individual pedalling pattern regardless of the frame type. Such results can have important implications for training.